Analysis of Individual Characteristics of Employee’s Performance at Regional Hospital dr. Soebandi Jember on the Case of BPJS Inpatient Pending Claim - Demiawan Rachmatta Putro Mudiono; Atma Deharja; Erna Selviyanti; Widha Alamanda (Universitas Aisyah Pringsewu, 2023)
JKN program is mandatory social health insurance for all Indonesian citizens. JKN claims are submitted every month by the hospital to reimburse the service fee that has been provided to its participants. Pending claims occur because the submitted claims still get confirmation from the Social Security Administrator for Health. In March–May 2021, 234 pending claims were found out of 1934 total submitted inpatient claims by RSD dr. Soebandi Jember. This incident cannot be separated from the performance of claim officers. According to Gibson's theory, performance could be influenced by individual variables. The purpose of this study is to analyze the determinants of inpatient pending claims based on individual characteristics. This research a qualitative using depth interviews, observation, and documentation. The result shows pending claims caused by an unmatched ability of coders and physicians in charge of the patients, the implementation of internal verification has not been maximized and different perceptions regarding claims regulation between coders and BPJS verifiers. To solve the problem, an in-charge officer for the completeness of medical records in each inpatient room is needed, implement one-stop administration system, increase the understanding and accuracy of coder, and communicating with BPJS to equalize claims regulation perceptions. Abstrak: Program JKN merupakan asuransi kesehatan sosial yang bersifat wajib bagi seluruh penduduk Indonesia. Klaim JKN ditagihkan setiap bulan oleh rumah sakit untuk mendapatkan pergantian biaya atas pelayanan yang telah diberikan kepada pesertanya. Pending klaim terjadi akibat klaim yang telah diajukan masih mendapat konfirmasi dari BPJS Kesehatan. Jumlah pending klaim rawat inap RSD dr. Soebandi Jember pada bulan Maret-Mei 2021 ditemukan sebanyak 234 klaim (12,23%) dari total pengajuan 1914 berkas. Kejadian pending tidak terlepas dari kinerja pegawai yang terlibat dalam pengajuan klaim. Kinerja menurut teori Gibson dapat dipengaruhi oleh variabel individu. Penelitian ini bertujuan untuk menganalisis determinan kejadian pending klaim BPJS rawat inap berdasarkan variabel karakteristik individu. Jenis penelitian yaitu kualitatif dengan teknik pengumpulan data wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian determinan pending klaim rawat inap disebabkan adanya ketidaksesuaian kemampuan dan keterampilan petugas koding dan DPJP, pelaksanaan verifikasi internal belum maksimal, dan terdapat perbedaan persepsi terkait regulasi klaim antara koder dengan verifikator BPJS. Upaya perbaikan masalah tersebut yaitu perlunya penanggung jawab kelengkapan kuantitas pengisian rekam medis di setiap ruang rawat inap, penerapan sistem one stop administration, peningkatan pemahaman dan ketelitian petugas koding, melakukan komunikasi dengan BPJS untuk menyamakan persepsi regulasi klaim.